Peran Pola Asuh Authoritative terhadap Self-Efficacy Akademik Dimediasi Vigor pada Remaja - Mutiara Mirah Yunita; Ni Putu Ayu Trisna Dewi (Guidena)
This study aims to determine the role of authoritative parenting style on academic selfefficacy mediated by vigor. The research method used in this study is a quantitative method by using a questionnaire for data collection and involving 3 types of measuring instruments to measure the three variables studied. The analysis technique used is a multiple linear regression technique using SPSS Program to determine the role of mediators in the research conducted. The measuring instrument in this study used: (1) Parenting Styles and Dimension Questionnaire Short Version (PSDQ-Short Version) by only measuring authoritative parenting, (2) Level of Academic Self-Efficacy Scale, and (3) Shirom Melamed Vigor Measure. The three measuring instruments have been adapted into Indonesian and have good cronbach alpha from the results of reliability testing, so they can be used as data collection tools. This research involved 116 teenage respondents who live in Jakarta and are active students. From the results of the study, it is known that there is a partial mediation of vigor in the role of authoritative parenting on academic self-efficacy. Thus it can be concluded that H1 is accepted and H0 is rejected where vigor can act as a mediator of authoritative parenting towards academic self-efficacy.